2021
DOI: 10.1590/fst.26120
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chia seed on chemical properties and quality characteristics of regular and low-fat crackers

Abstract: As a direct consequence of understanding the importance of the relationship between health and food, the interest in healthy recipes has increased. In the present study, wheat flour was used to replace chia seed (CS) in the cracker formulation (control) at levels of 10, 20, and 30% (w/w) and fat content was reduced by 25, 50, and 75% for the production of low-fat crackers. The physicochemical, textural, sensorial properties of the crackers were investigated. It was determined that CS had high a dietary fiber (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Pohjanheimo et al [28] reported that flaxseed bread was softer and more elastic than the control samples. Consistent with the findings of this study (Table 2), several researchers have reported that the inclusion of chia and flax seeds in bakery and pastry products does not significantly impact the overall acceptability of the samples in terms of sensory evaluation [25,27,[29][30][31][32]. 3.9 (1.1) † 4.0 (1.0) † 3.6 (1.1) † 3.3 (0.9) † 3.9 (0.4) † 3.9 (0.4) † Chia-added 3.7 (1.3) † 4.1 (0.7) † 3.9 (0.9) † 4.1 (1.2) † 4.0 (0.6) † 4.0 (0.6) † Flaxseed-added 4.0 (1.4) † 4.3 (0.9) † 2.9 (1.3) † 4.1 (0.4) † 3.9 (1.1) † 3.9 (1.1) † Chia+Flaxseedadded 4.6 (0.5) † 4.1 (1.5) † 3.0 (1.3) † 4.1 (1.1) † 4.0 (1.2) † 4.0 (1.2) † † There is no difference between the groups with the same letter…”
Section: Sensory Analysis Resultssupporting
confidence: 91%
“…Pohjanheimo et al [28] reported that flaxseed bread was softer and more elastic than the control samples. Consistent with the findings of this study (Table 2), several researchers have reported that the inclusion of chia and flax seeds in bakery and pastry products does not significantly impact the overall acceptability of the samples in terms of sensory evaluation [25,27,[29][30][31][32]. 3.9 (1.1) † 4.0 (1.0) † 3.6 (1.1) † 3.3 (0.9) † 3.9 (0.4) † 3.9 (0.4) † Chia-added 3.7 (1.3) † 4.1 (0.7) † 3.9 (0.9) † 4.1 (1.2) † 4.0 (0.6) † 4.0 (0.6) † Flaxseed-added 4.0 (1.4) † 4.3 (0.9) † 2.9 (1.3) † 4.1 (0.4) † 3.9 (1.1) † 3.9 (1.1) † Chia+Flaxseedadded 4.6 (0.5) † 4.1 (1.5) † 3.0 (1.3) † 4.1 (1.1) † 4.0 (1.2) † 4.0 (1.2) † † There is no difference between the groups with the same letter…”
Section: Sensory Analysis Resultssupporting
confidence: 91%
“…As a part of this study, by CS replacement; dietary fiber, protein, and ash contents were increased for cracker samples; and the fatty acid content was were enriched in terms of linoleic, oleic, α-linolenic acids. C Dd was also expressed as the healthiest sample according to C 18:1 /C 18:0 ratio (Dundar et al, 2020). In this study, C Dd is also determined as the richest sample in terms of bioactive potential (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…CS is a good source for bakery products with high protein (21.78%) and dietary fibre (38.70%) contents, including fatty acid varieties (Dundar et al, 2020) together with its bioactive potential. As a part of this study, by CS replacement; dietary fiber, protein, and ash contents were increased for cracker samples; and the fatty acid content was were enriched in terms of linoleic, oleic, α-linolenic acids.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of fiber flax is due to the variety of its uses (Duman, 2022;Dundar et al, 2021;Ahmad et al, 2021). Fabrics for various purposes are produced from flax fiber: clothing (linen fabrics), household, furniture-decorative, industrial, as well as special-purpose fabrics (medical and defense industries).…”
Section: Methodsmentioning
confidence: 99%